Hyperdilution of CaHA fillers for the improvement of age and hereditary volume deficits in East Asian patients - Chao YYY; Kim JW; Kim JS; Ko H; Goldie K (Dove Medical Press, 2018)
Yates YY Chao,1 Jong Woo Kim,2 JongSeo Kim,3 Hyungseok Ko,4 Kate Goldie5 1Chao and Chiu Institute of Aesthetic Medicine, Taipei, Taiwan; 2IU Clinic, Seoul, Republic of Korea; 3Kim‑JongSeo Plastic Surgery Clinic, Seoul, Republic of Korea; 4Samsung Lohas Clinic, Jeonju, Republic of Korea; 5European Medical Aesthetics Ltd, London, UK Abstract: With their high elasticity and viscosity, calcium hydroxylapatite (CaHA) fillers are now widely used to treat age-related or hereditary facial soft tissue volume deficits. CaHA filler volume augmentation is further enhanced by its ability to stimulate neocollagenesis and improve skin quality. However, its high viscosity and cohesivity may hinder its spread and distribution, while its injection by cannula or needle may require moderate extrusion force and lead to uneven distribution or focal accumulation in tissues. Thus, new or modified delivery techniques and tools have emerged, particularly from East Asian physicians. One such technique is hyperdilution with diluents such as lidocaine or normal saline. CaHA hyperdilution appears to be more frequently used by experienced injectors who have varying methodologies. Here, we demonstrate the precise delivery of diluted filler to treat indications related to hereditary volume deficits, volume loss, or aging in the periorbital, nasolabial and submalar regions, marionette lines, and hollowed mid-facial areas. Regardless of age or indication, dilution eases filler delivery for the injector, while using lidocaine as the diluent decreases patient discomfort and minimizes pain. Increasing injection diluent volumes reduces filler thickness (viscosity) and facilitates its even spread, encouraging skin stimulation through more direct contact with tissues and minimizing unevenness. Our results effectively demonstrate that hyperdilution is an innovative and positive evolution in CaHA filler delivery. Keywords: CaHA, hyperdilution, skin regeneration, facial sculpting, facial volumization